Helfen und Wohlbefinden aus psychologischer Perspektive - Luhmann, Maike (Evangelische Theologie, 2021)
Psychological research has long been interested in whether helping can make people happy. This article summarizes empirical evidence and theoretical models on the relationship between helping and well-being. Empirical studies indicate a significant, but weak positive relationship between helping behaviors and well-being. The functional approach and self-determination theory are two theoretical frameworks that are particularly relevant for interdisciplinary investigations of this topic. The article concludes with a discussion of open questions and avenues for future research.